A mediação pedagógica na educação a distância: o caso da Licenciatura em Ciências Naturais da Universidade Federal da Paraíba - Lima, Jamile de Moura (2011)
Vygotsky was one of first, if not the first developmental theoretician who explored the notion of mediation in his theory. For this author, mediation occurs from the interposition of an external element (sign) between the individual and his/her behavior, and thus, modifying it. The sign will be used like an instrument in order to facilitate reality and individual‟s action apprehension about the world. Pedagogical mediation corresponds to the range of activities and behaviors starting from the teacher with a view to orient, structure, motivate, defy, research and render problematic, together with the student. The teacher disposes of an apparatus of technological, pedagogical and didactical resources (digital or not) to provide for an interactive, collaborative, dialoged learning process focusing on research, as well as an active construction of knowledge. In the realm of policies for teachers‟ graduation, especially the Open University system in Brazil, this study analyses pedagogical mediation in teaching-learning processes, in Natural Sciences Graduation courses (distance learning) in Federal University of Paraíba, which uses Virtual Learning Environment MOODLE as a technological resource in order to develop pedagogical practices. The case study approach, followed up by the interview and documental analysis technique, made up the data collecting tools. The analysis confirmed that the studied course does not present a cohesive and clear definition of Education and Distance Learning based on a pedagogical theory; it does not present clarity as for the comprehension of technologies and their uses, as well as there are no elements in the political pedagogical project of the course, and neither in professors‟ practice that point to an adherence to a pedagogical mediation pattern. Based on these grounds, the accomplished reading indicates that the pedagogical posture of the studied course professors is neither adequate for Distance Learning, nor is concrete for a mediating practice; rather, it suggests a mere transmission of contents, in which students‟ interaction and participation occur in a superficial way. It also accentuates that the course tutors and professors‟ tasks are not clear enough in the course project, which jeopardizes its functioning, subject-matters development as well as students‟ learning.